As negras de tabuleiro e os conflitos de rua no Recife dos oitocentos. - Silva, Rejane Maria Pereira da (2020)
Recife in the eighteenth period. This aims to investigate the normative and control practices over the work and life of black women (slaves and free), understanding the Law of Free Womb and mapping the speeches produced at the House of Detention in the city of Recife. In this work, we will use primary and secondary bibliographic source research, and ethnographic research. What we have in analysis is that black women were persecuted in the city, because they carried the mark of slavery. The ordering of the urban space and sanitation of the city promoted several conflicts and “Characteristics of rebellion” which triggered the entry of black women into the detention house.